2022
DOI: 10.3390/md20010061
|View full text |Cite
|
Sign up to set email alerts
|

Marine Collagen: A Promising Biomaterial for Wound Healing, Skin Anti-Aging, and Bone Regeneration

Abstract: Marine organisms harbor numerous bioactive substances that can be utilized in the pharmaceutical and cosmetic industries. Scientific research on various applications of collagen extracted from these organisms has become increasingly prevalent. Marine collagen can be used as a biomaterial because it is water soluble, metabolically compatible, and highly accessible. Upon review of the literature, it is evident that marine collagen is a versatile compound capable of healing skin injuries of varying severity, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 109 publications
1
74
0
2
Order By: Relevance
“…In addition, collagen significantly decreased the number of apoptotic chondrocytes and improved the status of the cartilage matrix. In agreement with ( Geahchan et al, 2022 ), collagen peptide ameliorates osteoarthritis progression by promoting extracellular matrix synthesis, promoting the formation of type II collagen ( Figure 4 ). This effect could very well be due to the absorption of functional peptides such as Gly-Pro-Hyp and Pro-Hyp by the body following oral administration of collagen peptides.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, collagen significantly decreased the number of apoptotic chondrocytes and improved the status of the cartilage matrix. In agreement with ( Geahchan et al, 2022 ), collagen peptide ameliorates osteoarthritis progression by promoting extracellular matrix synthesis, promoting the formation of type II collagen ( Figure 4 ). This effect could very well be due to the absorption of functional peptides such as Gly-Pro-Hyp and Pro-Hyp by the body following oral administration of collagen peptides.…”
Section: Discussionsupporting
confidence: 85%
“…Studies showed that supplementation of arginine nutrition can partially improve embryonic survival and development in mammals, including humans, pigs, sheep, and rats ( 45 , 46 ). The specific underlying mechanism of arginine actions remains unclear, and to date, most of the biomedical applications of fish skin peptides focus on wound healing, skin anti-aging, inflammation reduction, and bone regeneration ( 47 , 48 ). Therefore, the protective effect on fetuses may be an interesting and meaningful direction worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The interest in these naturally derived biopolymers in healthcare related sectors has had very fast growth in recent years. Collagen-based products obtained from marine organisms are considered compatible, pathogen free, and have no religious restrictions compared to mammalian collagen [ 23 , 24 ]. In addition, collagen extraction from by-products of fish processing industry, such as skin and scales, can significantly reduce environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, marine collagen and its derivatives have been reported to promote wound healing in vitro by improving cell proliferation and migration, up-regulating the expression of chemotactic factors (i.e., ÎČ-Fibroblast growth factors (FGFs) and Transforming growth factor (TGF)-ÎČ1), or important growth factors (i.e., Vascular endothelial growth factor (VEGF)) and stimulating the recruitment of inflammatory cells. Different formulations of collagen-based products, applied on wounded animal models, showed an increased re-epithelization rate, wound closure, and granular tissue deposition compared to control groups [ 24 , 31 ].…”
Section: Introductionmentioning
confidence: 99%